Zebrafish breeding in laboratory environment at TIFR (Journal of Laboratory Animal Science, 2024)
Laboratory zebrafish (Danio rerio) has proved promising vertebrate animal model in modern biology research during  past few decades. Several inherent biological features in zebrafish, have invited attention of the scientific community to  use them in genetics and developmental biology research. Attempts were made to establish facility to raise and maintain  several lines of wild type and mutant zebrafish at the Department of Biological Sciences in 2009. A small room in the  department housed ~50 wildtype zebrafish obtained from the ornamental fish shop at the local market (M/s. Vikrant  Aquaculture, Mumbai). At the beginning, fish were raised in glass aquarium of 50 liters capacity for 6 to 12 months.  During the period of initial setup, all the members of the group associated with the usage of zebrafish,received training  in the zebrafish husbandry, water quality control, fish breeding and health monitoring. The state of the art facility was  established later on by setting Recirculating Water System (RWS) procured from the Aquatic Habitat, USA. The wild  type (WT) and mutant fish lines procured from the Max Plank Institute (MPI), Germany,were kept in RWS after ensuring  healthy aquatic environment for the fish. The standard operating protocols for fish husbandry, breeding, nutrition, water  and health quality of zebrafish were formulated.The breeding parameters such as fecundity, egg spawning, viability and  mortality were studied. The female fecundity percentage noticed between 42 to 58 and the mean egg spawn found between  139.77 to 242.42 eggs per female in five strains. In-vitro culture of embryos revealed maximum mortality on first day of  culture with decreased mortality on subsequent days. Mortality percentage observed during the period of culture ranged  between 14.35 to 30.21 in five strains with mean mortality of 21.34%. The embryo viability in five strains ranged between  69.78% to 85.64% with mean viability of 78.65%. In the present study, attempts have been made to generate basic data  associated with breeding of the laboratory zebrafish.
Keywords: zebrafish; breeding; spawn; embryo; larva